Extending access to care across the rural US south: Preliminary results from the Alabama eHealth programme. (June 2019) - Jain, Kriti M; Bhat, Prashanth; Maulsby, Cathy; Andersen, Alexandria; Soto, Tomas; Tarrant, Ashley; Holtgrave, David R; Nortrup, Erin; Werner, Melissa; Dill, Laurie
Purpose: Using a mixed-methods formative evaluation, the purpose of this study was to provide a broad overview of the Alabama eHealth programme set-up and initial patient outcomes. The Alabama eHealth programme uses telemedicine to provide medical care to people living with HIV in rural Alabama. It was led by a community-based organisation, Medical Advocacy and Outreach (MAO), and supported by AIDS United and the Corporation for National Community Service's Social Innovation Fund with matching support from non-federal donors. Methods: We conducted and transcribed in-depth interviews with Alabama eHealth staff and then performed directed content analysis. We also tracked patients' ( n = 240) appointment attendance, CD4 counts, and viral loads. Findings: Staff described the steps taken to establish the programme, associated challenges (e.g., costly, inadequate broadband in rural areas), and technology enabling this programme (electronic medical records, telemedicine equipment). Of all enrolled patients, 76% were retained in care, 88% had antiretroviral therapy and 75% had a suppressed viral load. Among patients without missing data, 96% were retained in care, 97% used antiretroviral therapy and 93% had suppressed viral loads. There were no statistically significant demographic differences between those with and without missing data. Conclusions: Patients enrolled in a telemedicine programme evaluation successfully moved through the HIV continuum of care.